SIKAP ANGGOTA ORGANISASI SMK MA'ARIF 1 WATES KULON PROGO DALAM IMPLEMENTASI SISTEM MANAJEMEN MUTU ISO 9001:2008 - , Astuti Nurahmayanti ([Yogyakarta] : Universitas Gadjah Mada, 2013)
One school that is committed to ensuring its quality is SMK Maâarif 1 Wates Kulon Progo through participation in the implementation of ISO 9001:2008 Quality Management System of TUVRheinland Germany. ISO 9001:2008 QMS has eight principles including the involvement of people in need of awareness of all members of the organization to show the attitude of knowing, supportive, and willing to participate in the implementation of ISO 9001:2008 QMS. However, based on observations and interviews with several members of the organization, some of them are not aware of the activities in the implementation of ISO 9001:2008 QMS so we need a more in-depth study. To examine these issues, this study defined the central issue of how the attitude shown by the members of the organization SMK Maarif 1 Wates Kulon Progo associated with the implementation of ISO 9001:2008 QMS and also examines the differences in attitudes shown by each group member organization which consists of a group of teachers, staff, and students. This type of research is descriptive quantitative method. All members of the study population that is internal to the organization SMK Maâarif 1 Wates Kulon Progo Of the population, sample of 151 were taken. Data collection techniques in the form of primary data collection used a questionnaire that comes with the secondary data obtained through library and school database. Data were analyzed using descriptive analysis and ANOVA test track to find out the differences in attitudes shown by teachers, staff, and students. The results showed that employees have the highest value component of cognitive and conative attitudes of teachers and students. It shows employees have the knowledge and perception of the highest among the three, and employees also have the highest propensity to be willing to apply the rules in the implementation of ISO 9001:2008 QMS in SMK Maâarif 1 Wates Kulon Progo. Based on the results of the ANOVA test track, the affective component of organizational members of all three groups did not differ significantly, which means all three shows attitude and agree to receive ISO 9001:2008 QMS implementation in SMK Maâarif 1 Wates Kulon Progo. ANOVA test results also showed the path the three groups on all components of the organization's members tend to have a mean attitude in the high category of above 3.67.